2010
DOI: 10.1128/iai.00864-09
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Capsule and Lipopolysaccharide O Antigen in Interactions of Human Monocyte-Derived Dendritic Cells and Klebsiella pneumoniae

Abstract: In humans, Klebsiella pneumoniae is a saprophytic bacterium of the nasopharyngeal and intestinal mucosae that is also frequently responsible for severe nosocomial infections. Two major factors of virulence, capsular polysaccharide (CPS) and lipopolysaccharide (LPS) O antigen, are involved in mucosal colonization and the development of infections. These bacterial surface structures are likely to play major roles in interactions with the mucosal immune system, which are orchestrated by a network of surveillance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 47 publications
2
64
2
1
Order By: Relevance
“…Organisms such as Klebsiella pneumoniae evade DC binding through the production of an external polysaccharide capsule that masks the inherent pathogen-associated molecular patterns recognized by PRRs, resulting in decreased binding and internalization of the organism (77). In our studies, however, it is evident that DCs were able to bind the encapsulated C. gattii and internalize the organism, which was a process dependent on actin polymerization (49), indicating that the polysaccharide capsule of C. gattii was not inhibiting recognition or activation of these DC processes.…”
Section: Discussionmentioning
confidence: 99%
“…Organisms such as Klebsiella pneumoniae evade DC binding through the production of an external polysaccharide capsule that masks the inherent pathogen-associated molecular patterns recognized by PRRs, resulting in decreased binding and internalization of the organism (77). In our studies, however, it is evident that DCs were able to bind the encapsulated C. gattii and internalize the organism, which was a process dependent on actin polymerization (49), indicating that the polysaccharide capsule of C. gattii was not inhibiting recognition or activation of these DC processes.…”
Section: Discussionmentioning
confidence: 99%
“…Capsular K. pneumoniae strains are significantly less likely than acapsular strains to be phagocytosed by innate immune cells in both the presence and absence of opsonins (196). Capsule-mediated prevention of bacterial binding and internationalization by immune cells helps limit early inflammatory signals, resulting in a less robust induction of the immune response (242). Specifically, studies performed with K. pneumoniae-infected lungs found that capsular strains induced lower levels of the proinflammatory cytokines TNF-␣ and IL-6 and higher levels of the anti-inflammatory cytokine IL-10 than did acapsular strains (198,243).…”
Section: Capsulementioning
confidence: 99%
“…Hospital acquired K. pneumoniae infections have a 50% mortality rate if left untreated, largely due to the rapid acquisition of antibiotic resistance (Nordmann et al, 2009;Evrard et al, 2010). Given the clinical significance of this pathogen, knowledge of virulence factors other than the capsule and mechanisms of virulence are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…We focused on the membrane and vesicles from K. pneumoniae, a nosocomial pathogen associated with urinary tract infections, bacteremia, pneumonia, and pyogenic liver abscess (Podschun and Ullmann, 1998;Cancino-Diaz et al, 2000;Evrard et al, 2010;Hsieh et al, 2012). Hospital acquired K. pneumoniae infections have a 50% mortality rate if left untreated, largely due to the rapid acquisition of antibiotic resistance (Nordmann et al, 2009;Evrard et al, 2010).…”
Section: Introductionmentioning
confidence: 99%